Pseudanthessiid copepods (Cyclopoida) associated with Crinoids and Echinoids (echinodermata) in the tropical western Pacific Ocean. - Humes, Arthur G. (Smithsonian Institution Press, 1977)
Smithsonian contributions to zoology; no. 243